2004
DOI: 10.1159/000076418
|View full text |Cite
|
Sign up to set email alerts
|

Whole Deletion of CYP2A6 Gene <i>(CYP2A6*4C)</i> and Smoking Behavior

Abstract: The relationship between nicotine metabolism of CYP2A6 and the smoking behavior in a Japanese population was investigated. The CYP2A6 genotypes were determined by the PCR method. There was a significant difference in the frequency of the CYP2A6*4C allele, which is a whole deleted allele for the human CYP2A6 gene, between smokers and nonsmokers. The frequency of the CYP2A6*4C allele was higher in nonsmokers than in smokers, whereas the frequency of CYP2A6*1A/*1B heterozygotes with a higher activity of nicotine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…This may explain the lower CYP2A6*4 allele frequency reported here (Table 1) compared to a general smoking population. 15 The CYP2A6*4 allele has been associated with lower risk for being a smoker, reduced cigarette consumption and reduced risk for lung disease, [12][13][14]17 and thus it may be under-represented among treatment-seeking smokers, as participants in this study were long duration heavier smokers with a mean smoking duration of 30 years. In addition, among slow metabolizers in this treatment-seeking population, there was a greater percentage of women and those with fewer years of education compared to normal metabolizers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may explain the lower CYP2A6*4 allele frequency reported here (Table 1) compared to a general smoking population. 15 The CYP2A6*4 allele has been associated with lower risk for being a smoker, reduced cigarette consumption and reduced risk for lung disease, [12][13][14]17 and thus it may be under-represented among treatment-seeking smokers, as participants in this study were long duration heavier smokers with a mean smoking duration of 30 years. In addition, among slow metabolizers in this treatment-seeking population, there was a greater percentage of women and those with fewer years of education compared to normal metabolizers.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Variability in the rate of nicotine metabolism owing to CYP2A6 genetic polymorphisms may also influence nicotine plasma levels, 6,8,11 and a number of studies in adults have demonstrated that CYP2A6 genetic variation, causing reduced or absent enzyme activity, is associated with a reduced risk of being a smoker, lower amount smoked, altered smoking intensity and increased quitting. 8,[12][13][14][15][16][17] However, not all studies provide consistent results. [18][19][20] Investigations of the impact of CYP2A6 genotype on smoking behaviours usually recruit participants from the general smoking population or from cancer and health institutes.…”
Section: Introductionmentioning
confidence: 99%
“…A separate, but nonetheless important, issue is the relationship between variation in P450 genes and nicotine dependence. Polymorphism in CYP2A6, including gene deletion, has been shown in some studies to be associated with the likelihood of being a nonsmoker (Ando et al, 2003;Iwahashi et al, 2004;Pianezza et al, 1998;Sellers et al, 2000;Tyndale & Sellers, 2001). However, the association has not been confirmed in other studies (Schulz et al, 2001;Zhang et al, 2001).…”
Section: Figurementioning
confidence: 97%
“…It has become increasingly apparent that genetic variation in CYP2A6 contributes to the complexity of nicotine pharmacology [Malaiyandi et al, 2006], smoking etiology , and tobacco-related cancer risk [Fujieda et al, 2004]. For example, CYP2A6 variants that result in a decrease or a loss of enzyme function have been associated with smoking-related behaviors such as a decreased likelihood of being a current smoker [Iwahashi et al, 2004;Schoedel et al, 2004], lower cigarette consumption [Malaiyandi et al, 2006;Minematsu et al, 2006;Rao et al, 2000], and increased success in smoking cessation [Gu et al, 2000]. Of note, earlier studies did not uniformly find that CYP2A6 genotype associates with smoking behaviors [Carter et al, 2004].…”
Section: Introductionmentioning
confidence: 99%